Accessing public transportation service coverage by walking accessibility to public transportation under flow buffering. (June 2022) - Chen, Xiao; Pei, Tao; Song, Ci; Shu, Hua; Guo, Sihui; Wang, Xi; Liu, Yaxi; Chen, Jie; Zhou, Chenghu
Abstract: Traditional public transportation service coverage analysis focuses more on coverage at the origins. However, the accessibility at destinations also affects coverage. To address this issue, we propose a flow buffer method for analyzing public transportation service coverage, considering walking accessibility from both origins and destinations to the nearest station. We estimated population and volume coverages of metro stations using both proposed and traditional method with commuting flows extracted from mobile phone signaling data for Beijing in September 2018. The results show that coverages estimated using the proposed method significantly differ from those of the traditional method. At a distance threshold of 800 m, the traditional buffer, flow buffer with maximum distance, and flow buffer with additive distance showed population coverages of 32%, 16%, and 29%, respectively, and volume coverages of 15%, 2%, and 5%, respectively. When the distance thresholds were larger than 950 m, population coverages estimated by flow buffer with additive distance were larger than the traditional buffer. Apart from that, all other results estimated by flow buffer were lower than those of traditional buffer. Thus, previous coverage analyses were underestimated or overestimated. This approach encourages the consideration of urban transportation planning from the flow perspective. Highlights: A flow buffer method for measuring public transportation service coverage is proposed. This method considers both origin and destination to assess coverages. Flow buffer will change traditional results for the transportation service area.